A rare case of peri-implant distal radius fracture. (February 2021) - Stramazzo, Leonardo; Cioffi, Alessio; Rovere, Giuseppe; Vigni, Giulio Edoardo; Galvano, Nicolò; Sallì, Marcello; D'Arienzo, Antonio; Camarda, Lawrence; D'Arienzo, Michele
Abstract: A peri-implant fracture near the volar plate of distal radius represent a very rare injury. The main factor of this lesion is high energy trauma on the wrist. We report a case of a 61-year-old woman with a peri-implant fracture located just proximally to the plate and a fracture of the ulnar head that occurred after a simple fall. The patient was surgically treated by plate and screws removal. The fracture was fixed using a longer volar plate for the radial fracture and a plate for the head ulnar fracture. Different factors such as osteoporosis, BMI and screw position could influence the fracture pattern. However, considering growing use of plates for distal radius fracture fixation, the frequency of these kind of fracture will probably increase.